The effects of cadmium on plankton populations under different manurial treatments - A., Kaviraj; T. K., Kumar; T. K., Ghosal (Universiti Putra Malaysia Press, 1995)
Recovery of plankton populations from exposure to 1 mg/l of cadmium was studied in an outdoor bioassay using inorganic fertilizers, cow dung or poultry litter as nutrient additions. Although 99% oj the plankton populations were eliminated immediately after exposure to cadmium, both zoo- and phytoplankton densities began reappearing at a slow rate from Day 15 of treatment. Zoo plankton populations of the treated vats became numerically comparable to the control within 55 days of treatment. Poultry litter effected a quicker recovery of zooplankton populations. However, phytoplankton populations did not recover from the cadmium stress in any of the nutrient treatments even after 55 days. Dissolved cadmium was present in solution up to Day 15, while in the other treatments it persisted up to 25 days.